Utilization of Scratch in Mathematics Learning on Students' Computational Thinking Ability (Jurusan Matematika FMIPA UNNES, 2023)
To realize Indonesia Emas where today there has been digitalization in various field, so it is necessary to have computational thinking skills through mathematics learning. In learning mathematics, a learning media that is relevant to computational thinking skills is needed, namely Scratch. The purpose of this study is to conduct a literature study on the use of Scratch as a learning mathematics media for students’ computational thinking abitilies. This research method is a literature study with three stages, namely organizing, synthesize, and identify . Based on the results and discussion, it is found that the Scratch as a mathematics learning media has a very large influence on students’ computational thinking abilities. This is shown by development of computational thinking skills through Scratch as media for learning mathematics. The suggestion of this research is needed more research on the use of Scratch in mathematics learning on students’ computational thinking abilities in order to provide more innovative and optimal result.